PERTANGGUNG JAWABAN PIDANA PELAKU TINDAK PIDANA PEMERKOSAAN TERHADAP ANAK DI BAWAH UMUR KAITANNYA DENGAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Agustina Agustina (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT This thesis is entitled “CRIMINAL RESPONSIBILITY OF ACTION BEHAVIOR OF CRIMINAL RISK TO CHILDREN UNDER THE AGE OF RELATIONSHIP WITH LAW NUMBER 35 YEAR 2014 ON THE PROTECTION OF CHILDREN (STUDY COUNCIL OF CLASS 1A SAMARINDA)”, with 2 (two) principal issues that is :  What factors affect a person committing a criminal act of rape of a minor?How the form of legal liability for criminal rape of minors under Law No. 35 of 2014 on Child ProtectionThe study aims to determine the factors, accountability, and the application of sanctions for perpetrators of criminal acts of rape of minors, factors influencing perpetrators of criminal acts of rape include internal factors and external factors and accounbility received by perpetrators of criminal acts of rape of minors ie imprisonment for 5 (five) Years in reduced while the defendant is in ptison and a penalty of Rp. 3.000.000,- (three million rupiah) Subsidier 2 (two) months of confinement.  Keywords : Rape of Minors The Accounbility of The Perpetrators of The Criminal Act of Rape.